2021
DOI: 10.1097/cm9.0000000000001399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal biomechanics among primary open-angle glaucoma with normal tension or hypertension and controls

Abstract: Background:Normal tension glaucoma (NTG) is a less pressure-dependent type of glaucoma with characteristic optic neuropathy. Recently, the biomechanical mechanism has been thought to account for glaucomatous optic neuropathy to some degree. We intended to compare dynamic corneal response parameters (DCRs) among patients with primary open-angle glaucoma with normal tension or hypertension and controls. The correlations between DCRs and known risk factors for glaucoma were also analyzed.Methods:In this cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…We found that for HTG, there was no significant difference in DCRs between the groups with or without visual field progression. The results were consistent with previous observations that corneal biomechanical parameters were not significantly different between the HTG and normal groups ( Wei et al, 2021 ). Our results indicated that VF progression in the HTG group with a 30% decrease in IOP compared with the baseline IOP was not related to corneal biomechanics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that for HTG, there was no significant difference in DCRs between the groups with or without visual field progression. The results were consistent with previous observations that corneal biomechanical parameters were not significantly different between the HTG and normal groups ( Wei et al, 2021 ). Our results indicated that VF progression in the HTG group with a 30% decrease in IOP compared with the baseline IOP was not related to corneal biomechanics.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that the progressive group had a greater corneal depression depth, displacement area and flattening length at the first applanation than the nonprogressive group, which might indicate that the progressive group had a more deformable cornea. As previous studies ( Li et al, 2017 ; Wei et al, 2021 ; Wu et al, 2022 ) indicated that cornea biomechanics were related with age, sex, CCT, AL, IOP, and glaucoma severity, these factors were adjusted in the analysis. In baseline comparisons, MD in the progressive group (−10.33 dB) was lower than that of the nonprogressive group (MD: −5.57 dB), while the difference was not significant ( p = 0.254).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, SSI and SP-A1 showed corneal stiffness changes and decreased significantly after pharmacotherapy. Consistent with the findings of previous research, A1L, A2L, HCT, and HCR infrequently showed no significant changes after long-term pharmacotherapy or at an early stage after surgery [ 2 , 8 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Biomechanical mechanisms are thought to partly explain glaucoma optic neuropathy, Wei et al [ 21 ] analyzed dynamic corneal response parameters by comparing normal-tension glaucoma subjects, hypertension glaucoma subjects, and control subjects. Results showed that the corneal deformation of normal-tension glaucoma was more pronounced than in hypertension glaucoma or the control group, people with hypertension glaucoma showed no significant difference in corneal deformation ability compared with the control group.…”
Section: Biomechanical Analysis Of Ocular Diseasesmentioning
confidence: 99%